The Paradox of Ramadan Happiness in Palestine: A Peircean Semiotic Analysis of Zain’s Public Service Advertisements - Umarotul Mahdy; Dien Nur Chotimah (Journal of Islamic Communication and Counseling, 2026)
This study aims to reveal the meaning behind the signs used in advertisements that represent the happiness of Palestinians welcoming Ramadan amid the sorrow of war. The research employs a descriptive qualitative method, with data collected through observation and screenshots of the advertisements. The analytical framework is based on Peirce’s semiotic theory, which consists of the representamen, object, and interpretant. The findings show that the happiness associated with Ramadan is represented through joyful expressions and shared activities, such as playing, eating together, gathering with family, and acts of solidarity. Meanwhile, sadness is represented through images of destroyed urban buildings, forms of resistance, and issues related to the suffering of residents, particularly children. These findings indicate that Ramadan in Palestinian media representations not only conveys nuances of happiness and tranquility but also functions as a medium for articulating issues of resistance against Zionist Israel.